The role of financial exclusion in weakening the performance of banks: dynamic panel data analysis in Algeria and Tunisia. (16th January 2020) - Douma, Hasnia; Bettioui, Nesrine; Bendob, Ali
In the East and North Africa region, nearly 70% of adults (168 million) do not report any ownership of the account in the Arab world, which is lagging behind other regions. The importance of financial inclusion lies in its impact on the economy of countries, economic growth, financial sector development, and improving financial sector stability. This study aims to diagnose the relationship between financial inclusion and performance of banks in Algeria and Tunisia during 2004-2012 by using the panel data and the GMM method. Our results under static or dynamic panel data analysis show the negative impact of financial inclusion on profitability indicators (ROA, ROE and NIM). We conclude that financial inclusion decreases the profitability of banks. This result reinforces the role of lack of financial inclusion or financial exclusion in the non-development of the banking sector and the non-promotion of economic growth in Algeria and Tunisia.